Joint production cost comparison of electricity and heat using natural gas and glycerol - Quispe Gonzáles, C. A. (2012)
This work shows a thermodynamical analysis of a simplified cogeneration system for combined production of electricity and proccess heat. Due to increase of energetic demands, we propose a themodynamics schema based on a steam turbin working in conditions of thermic parity. We describe the thermal and thermal-economics calculations methodology of the system. We compare the thermaleconomics indexes using two types of combustible: natural gas and glycerol (methyled), and through the results obtained, is possible to compare the joint production prices of electricity and heat for the two combustibles proposed.